2019
DOI: 10.1111/hepr.13430
|View full text |Cite
|
Sign up to set email alerts
|

Zinc deficiency as an independent prognostic factor for patients with early hepatocellular carcinoma due to hepatitis virus

Abstract: Although a reduced serum zinc level is often observed in patients with chronic liver disease due to hepatitis virus, its prognostic importance has not been adequately investigated. This study aimed to elucidate the association of zinc deficiency with prognosis, especially in early hepatocellular carcinoma (HCC) patients. Methods: From 2005 to 2018, 466 patients with naïve HCC due to hepatitis virus were enrolled (327 men, 139 women; median age 70 years; hepatitis C virus [HCV] n = 389, hepatitis B virus [HBV] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…Thus, Zn supplementation in patients with chronic hepatitis C and liver cirrhosis improved liver function and long-term outcome, such as lower cumulative incidence of liver cancer. With the same aspect, poor survival in chronic viral patients with early HCC was significantly associated with Zn deficiency as well as incomplete infection control of the hepatitis virus [ 22 ]. The risk of esophageal variceal bleeding, the fatal complication of decompensated cirrhosis, was also correlated with the decreased level of Zn in patients with chronic viral hepatitis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Zn supplementation in patients with chronic hepatitis C and liver cirrhosis improved liver function and long-term outcome, such as lower cumulative incidence of liver cancer. With the same aspect, poor survival in chronic viral patients with early HCC was significantly associated with Zn deficiency as well as incomplete infection control of the hepatitis virus [ 22 ]. The risk of esophageal variceal bleeding, the fatal complication of decompensated cirrhosis, was also correlated with the decreased level of Zn in patients with chronic viral hepatitis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum MT levels were correlated with the Cu/Zn ratio (p = 0.046; Fig 2O), but not Cu or Zn levels taken independently (Fig 2P and 2Q). Previous studies have shown that excess Cu and Zn deficiency were associated with HCC with viral hepatitis [5,9]. Associations between the Cu, Zn, Cu/Zn and MT levels and other test values with or without hepatitis virus are shown in S1 or S2 Figs, respectively.…”
Section: Associations Between the Cu/zn Ratio And Other Test Values (mentioning
confidence: 95%
“…In contrast, Zn deficiency was reported to be associated with increased liver fibrosis [6,7] and hepatocarcinogenesis in patients with hepatitis C-related liver cirrhosis [8]. Recently, Hiraoka et al reported that Zn deficiency is an independent prognostic factor for early stage HCC patients infected with viral hepatitis who are receiving antiviral therapy [9]. The Cu/Zn ratio has been observed to be elevated in patients with hepatitis, liver cirrhosis or HCC and appears to be correlated with the overall severity of liver disease [4,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, there is growing evidence that hypozincemia may be associated with human hepatocarcinogenesis in patients with hepatitis C, and it is also an independent poor prognostic factor for patients with early hepatocellular carcinoma. 2,3 Physicians should be aware of this zinc deficiency-related cutaneous disorder in patients with hepatitis C virus, because it may be a poor prognostic sign in such patients. Keywords: Hepatitis C; Hepatocellular Carcinoma; Necrolytic Acral Erythema.…”
Section: Answer To Image (Page 38): Necrolytic Acral Erythemamentioning
confidence: 99%